Beaver dams maintain fish biodiversity by increasing habitat heterogeneity throughout a low‐gradient stream network. (26th April 2013) - Smith, Joseph M.; Mather, Martha E.
Summary Understanding the relationship between heterogeneity and biodiversity is an active focus of ecological research. Although habitat heterogeneity is conceptually linked to biodiversity, the amount and configuration of heterogeneity that maintains biodiversity within ecosystems is not well understood, especially for an entire stream network. Here, we tested alternative outcomes about how habitat alterations caused by beaver dams affected native fish biodiversity. Specifically, we quantified in‐stream habitat and fish assemblages above and below all beaver dams (n = 15) and selected control sites (n = 9), adjacent to beaver dams, within an entire, low‐gradient stream network (Fish Brook, MA, U.S.A.). Beaver dams altered habitat within streams in four ways based on upstream versus downstream differences in stream width, depth, velocity and substratum. In general, habitat heterogeneity, measured using two indices, was greater at beaver dams than control sites. The diversity and abundance of fish around beaver dams were positively related to habitat heterogeneity. Faster water and the coarser substratum below beaver dams increased the amount of fluvial habitat available to native fish. This alteration can be critical for fish with life histories that depend on flowing water and hard substrata. In summary, within a stream network, beaver dams maintained fish biodiversity by altering in‐stream habitat and increasing habitat heterogeneity. Understanding the relationship between habitat heterogeneity and biodiversity can advance basic freshwater ecology and provide science‐based support for applied aquatic conservation.